2003
DOI: 10.1590/s1516-89132003000200021
|View full text |Cite
|
Sign up to set email alerts
|

[No Title Available]

Abstract: Six circulating hemocytes cell types from Diatraea saccharalis (Fabricius) (Lepidoptera: Pyralidae) larvae were identified by transmission and scanning electron microscope: prohemocytes (PR), plasmatocytes (PL) granulocytes (GR), spherulocytes (SP), oenocytoids (OE) and vermicytes (VE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In their investigation on hemocytes of the same insect, Kalia et al (2001) with phase contrast microscopy observed ADs, which had not been previously reported but considered as CGs (Essawy et al, 1985) or GRs (Gupta, 1994). Six types of hemocytes were identified in the sugarcane borer Diatraea saccharalis (Falleiros et al, 2003) and the lemon butterfly Papilio demoleus (Jalali and Salehi, 2008). Six hemocyte types were distinguished in all developmental stages of the variegated grasshopper Zonocerus variegates, namely PRs, PLs, GRs, SPs, OEs and ADs (Ademolu et al, 2010).…”
Section: Six Types Of Hemocytesmentioning
confidence: 99%
“…In their investigation on hemocytes of the same insect, Kalia et al (2001) with phase contrast microscopy observed ADs, which had not been previously reported but considered as CGs (Essawy et al, 1985) or GRs (Gupta, 1994). Six types of hemocytes were identified in the sugarcane borer Diatraea saccharalis (Falleiros et al, 2003) and the lemon butterfly Papilio demoleus (Jalali and Salehi, 2008). Six hemocyte types were distinguished in all developmental stages of the variegated grasshopper Zonocerus variegates, namely PRs, PLs, GRs, SPs, OEs and ADs (Ademolu et al, 2010).…”
Section: Six Types Of Hemocytesmentioning
confidence: 99%
“…The toxicity of methylmercury (MeHg) could adversely impact the survival of the animals, lowering their resistance to stress. The hemocytes circulating in the hemolymph represent the early defensive lineage acting through phagocytosis, nodulation, encapsulation, cytotoxicity and hemolymph coagulation (Falleiros et al 2003;Parisi and Cammarata 2014;Parrinello et al 2016). About that, the viability, the physiology, the numbers and ratio of the different kinds of hemocytes are very important for homeostasis.…”
Section: Introductionmentioning
confidence: 99%